Private Financing and Human Resource Practices of Small Local and Foreign-Owned Cosmetological Businesses - Patient Rambe (Journal of Economics and Behavioral Studies, 2017)
There exists a growing body of empirical studies that explore both the sources of small, micro and medium enterprises (SMME) funding, and the quality of their human resource practices. However, there is paucity of literature that interrogates the impact of private funding of local and foreign SMMEs on the quality of human resources. Nevertheless, the wide recognition of the economic significance of SMMEs in emerging economies and the pivotal role that funding plays in the growth of such firms suggest that the nexus between SMME private funding and human resourcing is integral to this condition and growth. As a result, the current study examined the influence of private financing of local and foreign-owned hair salon SMMEs on the quality of their human resources, in an attempt to bridge the aforementioned research gap. The study, which drew on a quantitative approach, is based on a survey conducted on 150 South African and foreign immigrant-owned hair salon businesses. The findings suggest that the private financing structure was dominated by a combination of debt and equity financing, followed by debt financing, with equity financing as the least employed funding model. The study established the significant impact that access to private equity financing has on recruitment, selection and compensation. However, the level of private debt financing, attractiveness of interest rates for private debt financing and financial value of funding from private institutions (banks) do not have any impact on human resources management practices. A major observation from the results is that, some aspects of private financing impact negatively on human resources management albeit a small effect size, which somehow raises critical questions about the popular claims that financing, contributes positively to the quality of human resources of firms.